“Some Unholy Alloy”: Neoliberalism, Digital Modernity, and the Mechanics of Globalized Capital in Cormac McCarthy’s The Counselor - David Deacon (European Journal of American Studies)
This article proposes a reading of The Counselor (2013) as an extrapolation of the frontier ethic animating much of Cormac McCarthy’s earlier writing. I will propose that echoes of Blood Meridian (1985), which presented the duality of barbarism and capital, are audible and perpetuated under digital capitalism, a condition encompassing the expansion of increasingly impersonal and anonymized capital under neoliberal socio-economics, empowered by digital globalization. Thus, the screenplay extends classic McCarthian themes, while expanding the remit of critique to class relations in contemporary cross-border, and global consumer economies. The subversive appetites of Western consumerism—focused around commodity fetishism and narcotics—symbolized by characters like Westray, Reiner, and Malkina, render a distinctly modern tragedy enabling a critique of how (and whether) it is possible to represent and oppose such a system of increasing ephemerality and correlative persuasion.